2021
DOI: 10.1038/s41467-020-20852-3
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of X-linked coding variation to severe developmental disorders

Abstract: Over 130 X-linked genes have been robustly associated with developmental disorders, and X-linked causes have been hypothesised to underlie the higher developmental disorder rates in males. Here, we evaluate the burden of X-linked coding variation in 11,044 developmental disorder patients, and find a similar rate of X-linked causes in males and females (6.0% and 6.9%, respectively), indicating that such variants do not account for the 1.4-fold male bias. We develop an improved strategy to detect X-linked develo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 72 publications
0
22
0
Order By: Relevance
“…Although the proportion of X-linked genes involved in neurodevelopmental disorders is recognized to be higher than autosomal genes, less is known about the specific effects of many rare X-linked variants in complex traits such as cognition. [41] The PLXNA3 predicted deleterious missense variants in our subjects are either novel or have a very low allele frequencies (less than 1/10,000) and thus the power of the loss-of-function observed/expected upper bound fraction (LOEUF) metric (currently estimated as 0.384 for PLXNA3) is limited. However, the probability of loss-of-function intolerance (pLI ≥ 0.9) metric for PLXNA3 predicts a high level of constraint.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…Although the proportion of X-linked genes involved in neurodevelopmental disorders is recognized to be higher than autosomal genes, less is known about the specific effects of many rare X-linked variants in complex traits such as cognition. [41] The PLXNA3 predicted deleterious missense variants in our subjects are either novel or have a very low allele frequencies (less than 1/10,000) and thus the power of the loss-of-function observed/expected upper bound fraction (LOEUF) metric (currently estimated as 0.384 for PLXNA3) is limited. However, the probability of loss-of-function intolerance (pLI ≥ 0.9) metric for PLXNA3 predicts a high level of constraint.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…Several mechanisms might cause this bias, including sex hormones, as suggested for testosterone exposure in fetal life in ASD ( Baron-Cohen et al, 2015 ). Possible genetic mechanisms underlying this gender seem not to involve X-linked variants, since X-linked ID is too rare to account for the 30% excess of males with this disorder and a recent burden analysis on a large group of patients with NDDs reported that X-linked causal variants were carried in similar proportions of males (6%) and females (6.9%) ( Martin et al, 2021 ). Our panel allows good coverage of X-linked genes, since it includes 67 of the 130 X-linked genes that have been implicated in NNDs, and detected X-linked variants in two males and 10 females, with seven originated de novo .…”
Section: Discussionmentioning
confidence: 99%
“…Due to insufficient information in population data banks and challenges in classifying inherited X-linked variants, most TAF1 variants have unknown significance. 24 This family shows how consanguinity can obscure alternative inheritance patterns. We couldn't classify this variant as pathogenic without segregation analysis, which emphasizes the need to store index, parent, and affected family DNA samples.…”
Section: Examples Of Lessons Learntmentioning
confidence: 99%